An efficient distributed algorithm for economic dispatch considering communication asynchrony and time delays. Issue 4 (30th August 2022) - Wang, Zheng; Chen, Guo; Li, Huaqing
Abstract: The increasing integration of distributed energy resources (DERs) to power grids has fostered the emergence of advanced control technologies for energy management. This study focuses on distributed solutions to economic dispatch considering asynchrony and non‐ideal communications. A distributed consensus‐based algorithm is developed for general directed networks, where heavy‐ball momentum is incorporated into the algorithm design to accelerate convergency. Subsequently, an asynchronous version is proposed based on a general asynchronous communication model with unpredictable, non‐uniform, and bounded time delays. Without a global clock in conventional synchronous distributed algorithms, distributed generators (DGs) are allowed to exchange information through local communications at any moment and use out‐sync information to execute new updates. Simulations are presented to demonstrate the performance of the proposed algorithm and verify its robustness against time delays.